2009
DOI: 10.1007/s11431-009-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and assessment on mountain tunnels and geotechnical damage after the Wenchuan earthquake

Abstract: On May 12, 2008, a strong earthquake with a magnitude of 8.0 (Ms) struck Wenchuan town, in the eastern Sichuan area of west China. Following the earthquake on May 18, the Southwest Jiaotong University organized a damage survey team and dispatched it to the affected area for the investigation into the damage and collection of information and data. This paper outlines the findings of this investigation on the earthquake disaster to mountain tunnels and geotechnical engineering. The systematic investigation, invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
71
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(74 citation statements)
references
References 3 publications
(3 reference statements)
1
71
0
2
Order By: Relevance
“…Tunnel linings are often shown to be partly cracked following strong vibrations and there is an increased interest in identifying the complex damage mechanisms. For example, following the 2008 Wenchuan earthquake, over 30 tunnel linings were reported to have cracked with different types of cracks found in almost all the tunnel linings (Wang et al, 2009). It was found that longitudinal cracks observed in some tunnels developed and extended along the whole tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…Tunnel linings are often shown to be partly cracked following strong vibrations and there is an increased interest in identifying the complex damage mechanisms. For example, following the 2008 Wenchuan earthquake, over 30 tunnel linings were reported to have cracked with different types of cracks found in almost all the tunnel linings (Wang et al, 2009). It was found that longitudinal cracks observed in some tunnels developed and extended along the whole tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…On May 12, 2008, a violent earthquake struck Wenchuan town and destroyed many tunnels to various degrees in the region, and the tunnel damage in the portal section was particularly serious (Wang et al, 2009). So, the dynamic response of underground structures to earthquakes emerges as significant research direction.…”
Section: Introductionmentioning
confidence: 99%
“…During the Kobe earthquake in Japan in 1995, underground structures, such as the Daika subway station, were destroyed severely (Nishiyama, Kawama, & Haya, 2004), while in 1999 during the Chichi earthquake in Taiwan, 49 out of 57 mountain tunnels were destroyed to some extent (Wang et al, 2001). In 2008, during the Wenchuan earthquake in China, 56 tunnels were damaged and required retrofitting (Wang, Gao, Jiang, & Yuan, 2009). Subsequent investigations and analyses revealed that the damages of the pertinent tunnels related closely to the geotechnical conditions of the surrounding soil -rock deposits.…”
Section: Introductionmentioning
confidence: 99%